A Greatly Useful of GABA for Health - ทองเอกแก้ว จันทรพร (KKU Science Journal, 2015)
-aminobutyrate or GABA is synthesized from glutamate using the reaction of decarbaxylation. It is the chief inhibitory neurotransmitter in the mammalian central nervous system. It plays a role in regulating neuronal excitability throughout the nervous system that makes human brain relaxing and anti-anxiety. GABA is also directly responsible for anterior pituitary encouraged which increases the amount of human growth hormone and the regulation of muscle tone. In medicine, GABA is used for some neurological disorder treatment such as sleep disorder, anxiety and epilepsy by oral administration. There is also more scientifically and medicinally relevant evidence that GABA has a blood-pressure-lowering effect, low density lipoprotein-lowering effect, preventive effect on Alzheimer’s disease and an inhibitory action on leukemia cell proliferation and has a stimulatory action on the cancer cell apoptosis.